2013
DOI: 10.1039/c3dt50177a
|View full text |Cite
|
Sign up to set email alerts
|

Tetraanionic N2O2-coordinating ligands as potential building blocks for supramolecular magnetic networks

Abstract: A bisoxamate ligand containing three different types of coordination sites was designed and synthesized. The developed synthetic strategy was adopted to prepare a related 1,2-bis(2-hydroxybenzamido)benzene-derived ligand. Nickel(II) complexes of both the novel ligands were obtained and characterized by X-ray crystallography, NMR, electronic absorption spectroscopy, and theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The Ni 2+ cation is coordinated by two deprotonated amido N atoms and two carboxylate O atoms, resulting in a slightly distorted square-planar coordination geometry. In agreement with related nickel compounds, the Ni-N bonds are significantly shorter than the Ni-O bonds, which is due to the stronger donicity of the amido nitrogens (Fettouhi et al, 1996;Rü ffer et al, 2007aRü ffer et al, ,b, 2008Abdulmalic et al, 2013;Milek et al, 2013). Compared to the respective nickel complex without the CF 3 group (Abdulmalic et al, 2013), compound (I) exhibits longer Ni-N and Ni-O bonds.…”
Section: Structural Commentarysupporting
confidence: 79%
“…The Ni 2+ cation is coordinated by two deprotonated amido N atoms and two carboxylate O atoms, resulting in a slightly distorted square-planar coordination geometry. In agreement with related nickel compounds, the Ni-N bonds are significantly shorter than the Ni-O bonds, which is due to the stronger donicity of the amido nitrogens (Fettouhi et al, 1996;Rü ffer et al, 2007aRü ffer et al, ,b, 2008Abdulmalic et al, 2013;Milek et al, 2013). Compared to the respective nickel complex without the CF 3 group (Abdulmalic et al, 2013), compound (I) exhibits longer Ni-N and Ni-O bonds.…”
Section: Structural Commentarysupporting
confidence: 79%
“…These results suggest that 2 potentially undergoes a fast photochromic reaction due to a decrease of Ea based on an increase of E by introducing of benzene ring with high aromatic stabilization energy to the ethene bridge. Although non-fluorinated DAB and its derivatives have been previously synthesized, 35,36 there have been no studies on their photocyclization reactivities. In a recent work, Milić et al assumed that the photocyclization of DABs may be prohibited owing to the high aromaticity of the benzene ring.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…DAE photoswitches based on π-linkers that are part of an aromatic ring (such as 4 , Scheme b) are highly desirable for the functionalization of complex molecular materials, but remain scarcely investigated. Aromatic DAEs containing phenanthrene , and phenanthroline ,, moieties, which were developed by Walko and Feringa ( 5 ) or Yam et al ( 6 ), were shown to operate under similar conditions to conventional DAE switches (Scheme c), while effectively mimicking olefinic systems in accordance with Clar’s rule of π-sextets, leaving the central core of these systems with lower aromatic delocalization of the electron density (Scheme c). In contrast, the phenyl–DAE systems are not reported to photocyclize (Scheme b), possibly due to the fact that this system is more aromatic and therefore “resistant” to photocyclization. Specifically, introducing an aromatic ring as a DAE linker is likely to decrease the photocyclization efficiency due to aromatic π-bond delocalization and the aromatic stabilization energy (ASE).…”
Section: Introductionmentioning
confidence: 99%